UPAYA MENINGKATKAN KEMAMPUAN MEMAHAMI BACAAN BAHASA JEPANG TINGKAT DASAR MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TEKNIK SCRIPT (Penelitian Tindakan Kelas pada Mahasiswa Semester II Prodi Pendidikan Bahasa Jepang Unnes) - Andy Moorad Oesman; Chevy Kusumah Wardhana (Universitas Diponegoro, 2013)
Abstract The purpose of this classroom action research is to improve the quality of teaching and learning process for Dokkai Shokyu Kohan (basic level of reading comprehension) which was held at the Japanese Language Education Program, Semarang State University. This is because in the course there is the unequal distribution of activity and participation of students in following the learning process. To overcome these problems, the application of Script Cooperative Learning Techniques in Dokkai Shokyu Kohan’s course regarded as the right solution. The application of this model of learning is more motivating the lecturer and students to interact actively in Dokkai Shokyu Kohan learning process. After going through two cycles, the positive results of the application this Technique Script is starting to look. The positive result is the improvement of the role of teachers and increasing the student activity and participation in lectures. In addition, the average value of student learning outcomes also increased. Keywords: Dokkai Shokyu Kohan, Cooperative Learning Technique Script